2015
DOI: 10.3390/jcm4050858
|View full text |Cite
|
Sign up to set email alerts
|

Immune Pathways in Atopic Dermatitis, and Definition of Biomarkers through Broad and Targeted Therapeutics

Abstract: Atopic dermatitis (AD) is the most common inflammatory skin disease. Recent research findings have provided an insight into the complex pathogenic mechanisms involved in this disease. Despite a rising prevalence, effective and safe therapeutics for patients with moderate-to-severe AD are still lacking. Biomarkers of lesional, nonlesional skin, and blood have been developed for baseline as well as after treatment with broad and specific treatments (i.e., cyclosporine A and dupilumab). These biomarkers will help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 100 publications
2
105
0
Order By: Relevance
“…Clinical assessment of AD lesions is often hampered by symptoms such as erythema and lichenification. Furthermore, as addressed by Mansouri and Guttman-Yassky [8], AD has a high placebo response rate, which might influence assessment of the efficacy of therapeutics in clinical trials. The profiles of inflammatory mediators in AD skin lesions during exacerbation or after treatment have been insufficiently investigated because most studies are based on blood samples, and thus only provide information on systemic profiles and not on the cutaneous microenvironment [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical assessment of AD lesions is often hampered by symptoms such as erythema and lichenification. Furthermore, as addressed by Mansouri and Guttman-Yassky [8], AD has a high placebo response rate, which might influence assessment of the efficacy of therapeutics in clinical trials. The profiles of inflammatory mediators in AD skin lesions during exacerbation or after treatment have been insufficiently investigated because most studies are based on blood samples, and thus only provide information on systemic profiles and not on the cutaneous microenvironment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This further emphasizes the interaction between the immune system and skin barrier in AD, particularly since flares of AD are characterized by activation of Th2 pathways [6,7]. The profile of inflammatory mediators might provide more insight into specific immunopathological pathways, offering potential targets for more personalized therapy, the subclassification of AD, and for the monitoring of therapy [8]. Clinical assessment of AD lesions is often hampered by symptoms such as erythema and lichenification.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic agents used in the management of AD mostly provide symptomatic relief, in the form of topical emollients and topical anti-inflammatory @ C I C E d i z i o n i I n t e r n a z i o n a l i agents, with limited, unspecific options for moderate-tosevere disease. However, emerging data on new antiinflammatory agents have been published in the recent years (18). New evidences point to an improvement in efficiency not so much in new molecules, but in the adequate combination of existing drugs.…”
Section: Discussionmentioning
confidence: 99%
“…These agents can individually and collectively provide significant relief for those with mild disease [7]; however, they are frequently inadequate for patients with moderate to severe disease, and studies have shown that most providers resort to intermittent courses of systemic steroids and, less commonly, phototherapy to manage this group. A remarkably small percentage of physicians utilize a host of systemic immunosuppressants, all of which are off label, as steroid-sparing agents in this more recalcitrant group [8,9]. Of the more commonly used systemic immunosuppressants, cyclosporine has the strongest evidence for efficacy in AD, but its long-term use is limited because of the relatively common side effects of hypertension and nephrotoxicity as well as a host of other less frequent complications, not the least of which is the increased risk of infections and malignancy [10].…”
Section: Introductionmentioning
confidence: 99%